Alamat ng sampaguita The legend of the sampaguita - Matias, Segundo D. (Lampara books, 2009)
"In the beginning of time, there were two sisters who were both beautiful and were always mistaken for twins--Saling and Sampaga. But because of a mysterious old woman, their lives took different courses. While Sampaga always won as queen of beauty in various festivities and became the object of fondness of the people, Saling was overcome with envy and planned to take away her sister's good fortune. Read in this contemporary legend the origin of the sampaguita, and how helpfulness is rewarded with the sweet fragrance of success while envy earns a corresponding penalty."